2016
DOI: 10.5468/ogs.2016.59.4.303
|View full text |Cite
|
Sign up to set email alerts
|

Reference values for the cervical length measurement in the second trimester of pregnancy using the transvaginal ultrasound in a large Brazilian population

Abstract: To establish reference values for the cervical length (CL) measurement by transvaginal ultrasound between 20 and 24+6 weeks of gestation in a large Brazilian population. A retrospective cross-sectional study was performed with 996 singleton pregnancies. The CL measurement (mm) using the transvaginal ultrasound was obtained in a sagittal view and the calipers positioned to measure the linear distance between the triangular area of echodensity at the external os and the internal os. The median±standard deviation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
(17 reference statements)
0
6
0
Order By: Relevance
“…This unusual finding could be related with the small sample size of our study or different characteristics of our population. In a recent study from our group which established reference values for CL measurement between 20 and 24+6 weeks of gestation in 996 singleton pregnancies, CL measurement did not modify significantly with gestational age [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…This unusual finding could be related with the small sample size of our study or different characteristics of our population. In a recent study from our group which established reference values for CL measurement between 20 and 24+6 weeks of gestation in 996 singleton pregnancies, CL measurement did not modify significantly with gestational age [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…A variety of nomograms have shown that CL is independent of gestational age at the mid-trimester ultrasound ( Table 2). 5,10,11,21,[25][26][27][28][29] There is considerable variability between published ranges, indicating specific variability of normal CL within different populations. 4 This underscores the need for the development of a local reference range.…”
Section: Reference Rangesmentioning
confidence: 99%
“…4 The most accurate cervical assessment method is the transvaginal ultrasound, which allows adequate observation of the internal and external cervical os and the endocervical canal, with a biometric precision of $ 100%. 5 The morphological and biometric study of the uterine cervix should be performed from the 14 th week of gestation onward because the ultrasonographic differentiation between the cervix and the lower uterine segment using ultrasound becomes difficult before this gestational age. 6 There is no consensus among authors regarding the value of cervical length that is considered short and the associated risk for premature labor, the reported values varying between 20 and 25 mm.…”
Section: Introductionmentioning
confidence: 99%